2001
DOI: 10.1097/00042560-200102010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention With Cotrimoxazole for HIV-1???Infected Adults: Results of the Pilot Study in Dakar, Senegal

Abstract: Our study does not show a beneficial effect of chemoprophylaxis with low-dose cotrimoxazole on survival or occurrence of opportunistic or nonopportunistic infections for HIV-1-infected patients in Dakar, Senegal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…21,23,24 Although we found relatively high rates of PCP with CD4 counts of 50 cells/KL or less, there was a nonsignificant trend toward a lower rate in blacks. 21,25 It is also possible that delays in PCP diagnosis, while ruling out TB and treating empirically for bacterial disease, may have underestimated the incidence rate with CD4 counts of more than 50 cells/KL. The results of this study suggest that targeted prophylaxis could have a large impact on reducing OIs, the reduction of which may be a key to reducing long-term mortality in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…21,23,24 Although we found relatively high rates of PCP with CD4 counts of 50 cells/KL or less, there was a nonsignificant trend toward a lower rate in blacks. 21,25 It is also possible that delays in PCP diagnosis, while ruling out TB and treating empirically for bacterial disease, may have underestimated the incidence rate with CD4 counts of more than 50 cells/KL. The results of this study suggest that targeted prophylaxis could have a large impact on reducing OIs, the reduction of which may be a key to reducing long-term mortality in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a small randomised clinical trial from Senegal was stopped early (because of the announcement of the WHO/UNAIDS recommendations 6 ); the authors concluded that chemoprophylaxis with low dose co-trimoxazole did not show a beneficial effect on survival or the occurrence of opportunistic or nonopportunistic infections. 7 The levels of resistance of locally relevant pathogens to co-trimoxazole was low in the Côte d'Ivoire studies, whereas much higher rates have been reported elsewhere. [8][9][10][11][12] Zambia has no policy on co-trimoxazole prophylaxis in people with HIV infection.…”
Section: Introductionmentioning
confidence: 87%
“…cause morbidity and mortality in African populations, suggesting wider benefits that possibly resulted from activity against various parasitic, fungal, and bacterial infections [2][3][4][5]. HIV/AIDS treatment guidelines recommend cotrimoxazole as a component of care for adults (including pregnant women) with low CD4 cell counts [6].…”
mentioning
confidence: 99%